Reverse Logistics and Competitive Advantage: The Mediating Effect of Operational Performance Among Manufacturing Firms in Kenya - Job, Mwanyota L.; Njihia, Muranga; Maalu, Jackson; Iraki, X.N. (European Scientific Journal, ESJ, 2020)
Today globally, countries and manufacturing entities alike are concerned with environmental sustainability apart from economic gains. Implementation of reverse logistics programs has been contemplated as a feasible alternative to mitigate the negative environmental effects of manufacturing while gaining competitory position. Literature has also suggested that improved operational performance results in the achievement of competitiveness. However the question has been whether implementing reverse logistics creates comparative advantage that leads to gaining competitive advantage for manufacturing entities. Specifically, the study sought to determine the influence of operational performance on the relationship between reverse logistics and a firm’s competitive advantage. Using correlation cross-sectional survey design, primary data were collected from 175 Kenya Association of Manufacturers (KAM) registered firms through a semi-structured questionnaire. Covariance-based, Structural Equation Modeling (SEM) was used to analyze the data and test the study hypothesis. Results from the hypothesis tests revealed that operational performance significantly mediates the association linking reverse logistics and a firm’s competitive advantage. The study confirmed that when resources are mobilized uniquely, they create comparative advantage consequently leading to competitive advantage. The study recommends that implementation of reverse logistics should be guided by a process that requires identifying the uniqueness of resources the organization has and strategically utilizing these resources in a manner that builds comparative advantage. Policymakers within the manufacturing sector in Kenya should improve the regulatory framework to upscale application of reverse logistics strategies in a manner that improves operational performance. Based on the limitations of the study, areas for further research have been suggested.